2010
DOI: 10.1002/jemt.20939
|View full text |Cite
|
Sign up to set email alerts
|

The effect of fluoride therapies on the morphology of bleached human dental enamel

Abstract: The aim of this in vitro study was to evaluate qualitatively the surface morphology of enamel bleached with 35% hydrogen peroxide (HP) followed by application of fluoridated agents. Forty intact pre molars were randomly distributed into four groups (n = 10), treated as follows: Group I (control group) remained stored in artificial saliva at 37 °C, Group II - 35% HP; Group III - 35% HP + acidulated fluoride (1.23%) and Group IV - 35% HP + neutral fluoride (2%). The experimental groups received three application… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
47
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 29 publications
1
47
0
1
Order By: Relevance
“…The images corresponding to the experimental groups show erosions and discontinuities on enamel surface compared to the control group. Others authors identified craters, depression areas, erosion, aprismatic layer removal and exposure of the enamel rods 24 . This may be explained by the radicals stemming from oxidizing agents, i.e., diffusion of them at about 100 ìm on the enamel surface 23 .…”
Section: Discussionmentioning
confidence: 99%
“…The images corresponding to the experimental groups show erosions and discontinuities on enamel surface compared to the control group. Others authors identified craters, depression areas, erosion, aprismatic layer removal and exposure of the enamel rods 24 . This may be explained by the radicals stemming from oxidizing agents, i.e., diffusion of them at about 100 ìm on the enamel surface 23 .…”
Section: Discussionmentioning
confidence: 99%
“…The morphological changes caused by the peroxides of high concentration are not evidenced macroscopically; however, microscopic changes, such as increased porosity, depressions, and superficial irregularities have been reported. 12 Studies have revealed mineral loss, increased susceptibility to erosion or caries, increased surface roughness; reduced enamel tensile strength, reduced fracture stability or a decrease in abrasion resistance of bleached enamel tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Although in-office bleaching is performed using high concentration hydrogen peroxide (15%-40%),12 it becomes a widely used procedure because of these advantages: Minimally invasive, immediate visible results and no need of patient cooperation 13. Also, in-office whitening is the best for patients who need close monitoring for clinical conditions such as pronounced gingival recession or deep, unrestored abfraction lesions, and necessary for tooth discolouration associated with endodontic therapy 2…”
Section: Introductionmentioning
confidence: 99%